**Answers:**

Are you solving for 't'? If so, this is how you solve for 't':

(2t - 1) / (t + 3)= -2

Move the (t + 3) to the other side of the equation:

=> 2t - 1 = -2(t + 3)

=> 2t - 1 = -2t - 6

Collect like terms and simplify:

=> 2t + 2t = 1 - 6

=> 4t = -5

=> t = -5/4

Therefore, t is -5/4.

t-1/3 = .2

t=.2+1/3

t=.533

[(2t-1)/ (t+3)=-2 ]t+3

=2t-1=-2t-6

= +2t +2t

=4t -1=-6

= 4t=-5

= t=-5/4

(2t-1) / (t+3) = -2

(2t-1) = -2(t+3)

2t-1 = -2t-6

2t+2t = -6+1

4t = -5

t = -5/4

t = -1.25

This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.

**More Questions & Answers...**